Efektivitas Program Sistem Administrasi Pedesaan (SIAP) Dalam Pelayanan Publik (Studi Pada: Desa Codo Kecamatan Wajak Kabupaten Malang): effectiveness, administration - Hari Purnomo (STISOSPOL WASKITA DHARMA, 2020)
The Effectiveness of the Rural Administration System Program (SIAP) in Public Services (Study on: Codo Village, Wajak District, Malang Regency) is the need of every citizen in terms of efficient and effective public services and care for every citizen's complaints. Currently, Indonesia is still a problem that is still being made improvements related to public services that are fast, effective and efficient. In order to improve public administration services, an administrative system is needed so that services run quickly, efficiently and effectively. The purpose of this study was to analyze the effectiveness of the Rural Administration System Program (SIAP) in public services, the research location was Codo Village, Wajak District, Malang Regency. This research method uses descriptive qualitative research methods. The results of this study indicate that the Rural Administration Program (SIAP) is very effective in providing public services for village administration, however, the Rural Administration Program (SIAP) still has several obstacles, namely the unavailability of adequate infrastructure or connection delays from all data service providers, causing the Rural Administration Program (SIAP) service was disrupted. Keywords: effectiveness, administration.